ORGANIZATION OF CULTURAL AND PUBLIC EVENTS IN FOREIGN COUNTRIES - Jumaev Husan Khudoyberdievich (Journal Park Publishing, 2024)
This article focuses on the concept of mass-cultural events and the innovative factors of organizing cultural events, as well as the study of foreign experiences in the organization of cultural events, the important aspects of organizing and managing cultural events abroad through international cultural relations.
Keywords: public-cultural events, innovation, spirituality, music, folk songs, speech art, renewal, rise, patriotism, spiritual-cultural holidays.